Hematological Analysis As Health Indicator Of (Epinephelus Sp.) Which Culture In Cages Of East Pangandaran Beach, West Java - Alipin, Kartiawati; Sari, Tresna Aulia (Metamorfosa: Journal of Biological Sciences, 2020)
Physiological changes caused by environmental stress and associated health status can be detected by haematological levels . This study aims to determine the health status of groupers (Epinephelus sp.) in the East Coast cage Pangandaran. The method used is observation method which includes the observation of location, sampling of fish, and interview with keramba owner and direct observation in the laboratory which includes identification of fish species, visual observation of fish, blood sampling, calculation of erythrocyte count, leucocytes, and measurement of hemoglobin . The data obtained were analyzed descriptively qualitatively presented in the form of tables and drawings. Observations showed that beautiful groupers (Epinephelus sp.) w ere the most cultivated fish and one of the most popular fish. This grouper has an erythrocyte count of 2.31 x 106 ± 1.79 cells / mm3, a leukocyte count of 226,325 x 103 ± 0.23 cells / mm3, and hemoglobin levels of 9.8 ± 2.8 gram%. Based on these data, it can be concluded that there is the beautiful grouper fish as unhealthy which cultivated in East Coast cages Pangandaran because the number of leukocytes that exceed the normal range and low hemoglobin levels.   Keywords: Hematology , Grouper, East Coast Pangandaran